O gênero textual carta argumentativa de reclamação no desenvolvimento da escrita autoral de estudantes da educação de jovens e adultos - Invenção, Arlene Ercília de Jesus (2021)
Mastery of reading and writing in literate societies is a basic condition for participatory, independent and empowered social action. In this scenario, the school, as a means of access to citizenship, has a fundamental role in the formation of critical readers and writers who are not characterized as mere reproducers of other people's ideas and texts, but who exercise social prominence when show own copyrights in their text production. However, not providing the individual the necessary conditions for him may to interpret his reality, consciously resorting to a series of procedures, is a way of excluding him from many sociocultural practices. Based on this assumption, this research work considers necessary to encourage critical reading from basic education, so that the student can prepare his own texts, aiming at authorial writing, while moving away from the culture of plagiarism. In this way, it is intended to develop teaching and learning strategies that promote critical literacy and authorship competence of a class of students from the 2nd stage/2nd level/YAE, Youth and Adult Education of Elementary school of the Education Reference Center of Youth and Adults Prof. Severino Uchôa, in Aracaju/SE, contributing to the formation of citizens capable of actively and ethically participating in cultural goods mediated by reading and writing, and to promoting the fight against plagiarism since basic education. The theoretical basis of this work follows studies on Reading and Writing as social practices (KLEIMAN, 1995; COULMAS, 2014), Critical Literacy (BARBOSA & MACIEL, 2018; FREIRE, 1996; ROJO, 2009) Authorship (FOUCAULT, 2009; CHARTIER, 2012; POSSENTI, 2009, 2013), Authorial Competence (ANTUNES, 2003, 2009; 2017, 2019; KOCH, 2009; 2015; 2016; 2018) and Plagiarism (KROKOSCZ, 2014; WACHOWICZ & COSTA, 2016; COSTA & LIMA, 2018). As a product for future intervention in teaching, a Pedagogical Notebook was created that presents a Didactic Sequence based on the proposal of Dolz, Noverraz and Schneuwly (2004), following the adaptation guided by Swiderski and Costa-Hübes (2009), from the textual genre letter complaint argument, whose production by the students will deal with the theme “quality of life, but its application was impossible because of the suspension of face-to- face classes due to the establishment of social isolation in the world, in this year of pandemic. Thus, it is expected as results, the development of attitudes aimed at the constitution of authorial competence. Thus, the relevance of this research is to contribute to the advancement of research related to writing skills, especially in YAE, with regard to the importance of critical reading for the production of texts, and seeking to solve the problem around the almost total lack of authorship in school texts and the practice of copying in this environment.